Authenticity and integrity of the Malagueira neighbourhood: Contribution to the nomination of Álvaro Siza’s works for the World Heritage List - Genin, Soraya M.; Pinto, P.; Krassavtse , A. (international conference Venice Charter [Re]Framed: New Heritage Challenges, 2024)
The Malagueira neighbourhood is Álvaro Siza's largest social housing project (1977) and represents a unique historical period in Portuguese architecture resulting from SAAL - Serviço Ambulatório de Apoio Local (1974-1976). It is part of a group of Siza's works for the World Heritage Tentative List, and is one of the properties proposed for future extension of the current nomination for the World Heritage List. Despite its undeniable historical, architectural and social value, it appears to be abandoned and degraded. The bibliography focuses mainly on historical and architectural issues, but conservation studies are lacking. This article aims to fill this gap by presenting work carried out as part of the “SizaAtlas research project. Filling the Gaps for World Heritage" and the Final Project of ISCTE's Integrated Master's Degree in Architecture, completed in 2023. The historical research revealed the complexity of the project, which was developed in several phases. The work remained unfinished, causing a series of urban voids. The methodology combines bibliographical and archival research with direct observation of the exterior of the buildings. The coverings and finishes of the façades were analysed and mapped, as were the elevations of the walls and constructions in the courtyards, the openings and frames of doors and windows, and the state of conservation of the buildings. The discussion compares it with Le Corbusier's Frugès neighbourhood. The results obtained prove the integrity and authenticity of the Malagueira neighbourhood.